Natural recreation and tourist resources of the Podilia region - Victoria Yavorska; Kateryna Kolomiyets; Diana Dianova; Olena Usatenko; Panas Karabadgak (Kazimierz Wielki University, 2018)
In the presented publication are analyzed natural tourist resources of the Podilia region. The ball estimation of natural resources is conducted for to the science-geographical areas. It is distinguished the most favorable and the least favorable science - geographical areas for recreation and tourist activity.